Regional geology of Czechoslovakia: geological atlas; 1:1,000,000; Neotektonicka mapa CSSR; Geological Map of Czechoslovakia; Tectonic Map of Czechoslovakia; Map of Quaternary and Residual Deposits of Czechoslovakia; Mineral Resources Map of Czechoslovakia; Metallogenetic Map of Czechoslovakia; Hydrogeological Map of Czechoslovakia; Aeromagnetic Map of Czechoslovakia - Kodym O. Odolen; Zarubova H. Helena (Prague, Geological Survey of Czechoslovakia, 1967)
Published by the Geological Survey of Czechoslovakia in co-operation with the Central Office of Geodesy and Cartography